Budget Efficiency and Service Effectiveness in CRM Digitalization: A Study of Satpol PP DKI Jakarta - Revi Majiza Putra; Hadi Prabowo; Hyronimus Rowa; Udaya Madjid (Department of Public Administration, 2026)
Digital transformation through the Citizen Relationship Management (CRM) system has significantly streamlined the administrative handling of public complaints within the Jakarta Provincial Civil Service Police Unit (Satpol PP). However, a high rate of recurring violations at the same locations indicates that administrative completion—marking a report as